Analysis of the Effectiveness of Four Variables in Men's Beach Tennis - Leonardo Pompéo Simon; Gustavo de Conti Teixeira Costa; João Victor Rosa de Freitas; Luiza Dutra Amador; Henrique de Oliveira Castro; Thiago José Leonardi; Lorenzo Laporta (Educación Física y Deporte)
This study examined the behavior of game actions and their connection to effectiveness in high-level men's beach tennis. A total of 7755 game actions (serves, returns, volleys, smashes, windmills, blocks, and defenses) from fifteen World Tour Sand Series matches in Valinhos were analyzed, along with their subvariables and trajectory types (lob, drop, straight, descending, and ascending). The direction, player positions, court zones, and action effectiveness were examined as well. A descriptive analysis of the data was complemented by a chi-square test with Monte Carlo correction to examine the association between tactical-technical variables and action effectiveness. Attacking shots were observed to be more effective than defensive ones, with a higher incidence in the center of the court. Attacking shots with descending trajectories were more effective than those with ascending trajectories or lobs and drops. This provides insights for strategies and training.